PENGARUH MODEL PEMBELAJARAN PREDICT OBSERVE EXPLAIN ((POE)) TERHADAP PENINGKATAN KETERAMPILAN SOSIAL SISWA SEKOLAH DASAR - Asthiyani Kholida; Nurdiansyah Nurdiansyah; Tiara Yogiarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Social skills are among the essential skills that need to be developed in social studies learning as they can foster responsibility, interaction-communication, cooperation, empathy-sympathy, self-control, and various other social aspects. However, the phenomenon observed indicates a still low level of social skills among elementary school students. The application of the Predict Observe Explain ((POE)) learning model is identical to science-based learning, but its implementation in social studies learning represents a new innovation to enhance social skills. This underpins the conduct of research in this thesis. The purpose of this study is 1) to determine whether the increase in social skills of students using the Predict Observe Explain ((POE)) learning model is better than that of students using the contextual learning model. 2) to find out the effect of using the Predict Observe Explain ((POE)) model on the improvement of social skills of elementary school students. The method used in this research is a quasi-experiment with a non-equivalent control group design on social studies learning material about the struggle of the Indonesian nation against colonialism and imperialism. The instrument used in the study was a social skills test. The results of the study from the n-gain score calculations showed that the experimental class had a score of 0.5320 and the control class also had a score of 0.3111. Furthermore, the results from the regression analysis indicated that the Predict Observe Explain ((POE)) learning model had an influence of 36,4%. The conclusions obtained from this study are: 1) There is an improvement in social skills among elementary school students using the Predict Observe Explain ((POE)) learning model compared to students using the contextual learning model; 2) There is an effect of the Predict Observe Explain ((POE)) learning model.